Terapi Resinkronisasi Jantung pada Penanganan Gagal Jantung - Hilman Zulkifli Amin; Siska Suridanda Danny (Jurnal Kardiologi Indonesia, 2015)
Heart failure (HF) is a worldwide health problem with high prevalence rate. The prevalence is over 23 million worldwide. It is a chronic disease characterized by the inability of the heart to pump an adequate amount of blood to achieve the demand of the different organ systems and/or doing so at increased filling pressures. Despite many recent advances in medication, the rate of people with HF is rising. This health challenges need to be answered properly. One of the new important treatment for HF is cardiac resynchronization therapy (CRT). Many patients with HF also have an abnormality of the heart’s electrical system resulting in asynchronous contraction pattern of heart muscle.The ultimate goal of CRT is to restore synchrony of the heart rhythm in HF patients. CRT implantation in heart failure patients with proper indications like wide QRS complexes, low left ventricular ejection fraction (LVEF), and left bundle branch block (LBBB) has been proved to reduce morbidity, mortality, and also improve symptoms and quality of life (QoL).